Exercise Hemodynamics and Quality of Life after Aortic Valve Replacement for Aortic Stenosis in the Elderly Using the Hancock II Bioprosthesis. (2nd December 2014) - Long, Theodore; Lopez, Becky M.; Berberian, Christopher; Cunningham, Mark J.; Starnes, Vaughn A.; Cohen, Robbin G.
Abstract : Background and Aim . While aortic valve replacement for aortic stenosis can be performed safely in elderly patients, there is a need for hemodynamic and quality of life evaluation to determine the value of aortic valve replacement in older patients who may have age-related activity limitation. Materials and Methods . We conducted a prospective evaluation of patients who underwent aortic valve replacement for aortic stenosis with the Hancock II porcine bioprosthesis. All patients underwent transthoracic echocardiography (TTE) and completed the RAND 36-Item Health Survey (SF-36) preoperatively and six months postoperatively. Results . From 2004 to 2007, 33 patients were enrolled with an average age of 75.3 ± 5.3 years (24 men and 9 women). Preoperatively, 27/33 (82%) were New York Heart Association (NYHA) Functional Classification 3, and postoperatively 27/33 (82%) were NYHA Functional Classification 1. Patients had a mean predicted maximumV O 2 (mL/kg/min) of 19.5 ± 4.3 and an actual maxV O 2 of 15.5 ± 3.9, which was 80% of the predictedV O 2 . Patients were found to have significant improvements (P ≤ 0.01 ) in six of the nine SF-36 health parameters. Conclusions . In our sample of elderly patients with aortic stenosis, replacing the aortic valve with a Hancock II bioprosthesis resulted in improved hemodynamics and quality of life.